1999
DOI: 10.1111/j.1572-0241.1999.1421_a.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflux Laryngitis: Pathophysiology, Diagnosis, and Management

Abstract: Gastroesophageal reflux disease is felt to be associated with a variety of laryngeal conditions and symptoms of which "reflux laryngitis" is perhaps the most common. The most likely mechanism for laryngeal injury and symptoms is secondary to direct acid and pepsin contact, although studies concerning the cause and effect between gastroesophageal reflux disease and laryngeal disorders are conflicting. Likewise, the most effective method to diagnose such patients is unclear. Empiric treatment of patients with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 35 publications
1
26
0
4
Order By: Relevance
“…Moreover, patients with oesophagitis are found to be at double risk of getting laryngitis than those who do not have it. 12 Harding and Richter 13 estimated the prevalence of GERD (Gastroesophagial reflux disease) associated cough and found it to be 10-40%. Classical symptoms of GERD are rarely presented these days by patients with GERD induced Otolarynologic manifestations making diagnosis of such cases more challenging in the present scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with oesophagitis are found to be at double risk of getting laryngitis than those who do not have it. 12 Harding and Richter 13 estimated the prevalence of GERD (Gastroesophagial reflux disease) associated cough and found it to be 10-40%. Classical symptoms of GERD are rarely presented these days by patients with GERD induced Otolarynologic manifestations making diagnosis of such cases more challenging in the present scenario.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the typical presentation of classic GERD laryngopharyngeal reflux (LPR) often results in atypical manifestations with oral, pharyngeal and pulmonary disorders. Concerning laryngeal symptoms, the most well-studied symptom is hoarseness [2,10,14,[16][17][18]. Several previous studies have demonstrated reflux of gastric acid into the pharynx in patients with chronic hoarseness [17].…”
Section: Laryngeal Disordersmentioning
confidence: 99%
“…The focus of most physicians and the lay public has been on those effects of gastroesophageal reflux associated with the esophagus [1]. Because of the anatomic proximity of the esophagus and the upper respiratory tract, it is not surprising that, in some patients with GERD, symp- toms attributable to the respiratory and upper aerodigestive tract may occur [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Woo et al [13] report that inflammatory conditions of the larynx commonly coexist with benign and malignant vocal fold lesions. Gastroesophageal reflux disease is also claimed to be associated with some benign laryngeal conditions [24,25]. The most common finding seen only in the reflux group was granulation of the posterior pharyngeal wall [26].…”
Section: Benign Vocal Cord Lesionsmentioning
confidence: 99%